Tenotomy or tenodesis for the long head of biceps lesions in shoulders: a systematic review and meta-analysis. - Heng'an Ge; Qiang Zhang; Yeqing Sun; Jie Li; Lin Sun; Biao Cheng (PLoS ONE)
Background Both tenotomy and tenodesis have been widely used for the treatment of long head of biceps tendon (LHBT) lesions, but the optimal strategy remains considerably controversial. In this meta-analysis of published studies, we compared the results of the two procedures. Methods A literature search that compared tenotomy with tenodesis was performed using MEDLINE, and Embase until August 2014. A total of 7 studies reporting data on 622 subjects were included. Study quality was evaluated using the PEDro critical appraisal tool and the NO quality assessment tool. Results Data synthesis showed higher functional outcomes, a lower complication rate, and longer surgical time in patients managed with tenodesis compared to tenotomy (Constant score, P = 0.02; Popeye sign, P < 0.001; cramp pain, P = 0.04; surgical time, P < 0.001, respectively). Conclusion This meta-analysis indicates that tenodesis results in better arm function and lower incidences of cramp pain and Popeye sign in LHBT lesions, while the procedure required longer surgical time compared to tenotomy. More sufficiently powered studies would be required to further determine the optimal strategy.